Practical limits of an optimized quantum receiver - Marquardt, Christoph; Müller, Christian R.; Leuchs, Gerd (Optics InfoBase Conference Papers, 2014)
We present a quantum receiver for the discrimination of quadrature phase-shift keyed signals that approaches the Helstrom bound for any signal power and discuss the influence of practical limitations. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05